H!FISH: Aquaculture dalam Aplikasi Sebagai Solusi Tepat pada Era Pandemic Covid19 - Rupi Sanjaya; Dzulfiqar Ammar Syam; Feldya D. Absharina; Madyasta A. Rarassari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Sanjaya R, Syam DA, Absharina FD, Rarassari MA. 2020. !FISH: Aquaculture in Application As The Right Solution in the Covid-19 Pandemic Era. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx: Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Covid19 Pandemic has impact starting to depress the national economy. The business sector is negatively affected, with a lot of employees being victimized by layoffs. This has an effect on the financial situation, thus encouraging people to rise up by taking entrepreneurial alternatives. H!FISH was presented as the right solution for covid19 Pandemic. The aims for this application to provide information and knowledge in the field of fisheries to people who have a desire to start entrepreneurial, given the abundant fishery resources. The advantages offered in the form of intensive and suistainable consultation from competent experts in the field of fisheries include aquaculture techniques, fish disease management, water quality management and fish nutrition. Consultation can be done from preparation to product marketing, even H! FISH will also provide special capital loans for people who want to be entrepreneurial fisheries. It is hoped that this innovation will be a breakthrough to help people affected by Covid19 and increase the skill to be professionally entrepreneurial and produce fish to meet the needs of independent food.